Impact of Cardiac Risk Factors on Complications Following Cranial Vault Remodeling: Analysis of the 2012 to 2016 National Safety Quality Improvement Program-Pediatric Database. Issue 2 (March 2019) - Bartz-Kurycki, Marisa; Wei, Shuyan; Bernardi, Karla; Moffitt, Joseph K.; Greives, Matthew R.
Abstract : Abstract: Congenital cardiac malformations have been reported in 8% of patients with craniosynostosis undergoing cranial vault remodeling (CVR), but associations with surgical outcomes are unknown. This study evaluated postoperative complications in patients who underwent CVR for craniosynostosis with or without cardiac risk factors (CRF) using the National Safety Quality Improvement Program-Pediatric (NSQIP-P) database. NSQIP-P database was queried for patients <2 years with craniosynostosis who underwent CVR from 2012 to 2016 based on diagnosis and procedure codes. The primary outcome was a composite of available NSQIP-P complications. Analysis compared patients with craniosynostosis based on the presence or absence of CRF. Univariate and multiple logistic regression identified risk factors associated with postoperative complications. A total of 3293 patients met inclusion criteria (8% with CRF). Two-thirds of patients experienced at least 1 complication, though patients with CRF experienced a greater proportion (74% vs 66%, P  = 0.001). Univariate analysis identified associations between post-operative complications and age, ASA class, supplemental oxygen, neuromuscular disorders, preoperative nutritional supplementation, interventricular hemorrhage, and CRF. On multivariate regression, only older age (OR 1.17, 95% CI 1.01–1.36) and longer operative duration (OR 1.01, 95% CI 1.01–1.01) were associated with greater odds of postoperative complications. The most common complication in patients with craniosynostosis who undergo CVR is bleeding requiring transfusion. Older age and longer operative duration were associated with postoperative complications. Although patients with CRF have more postoperative complications, CRF was not a risk factor on adjusted analysis.